The devil's punchbowl - Iles, Greg. (New York : Pocket Star Books, 2010)
Lawyer Penn Cage goes up against a mix of murder, racial tension, double-crosses, illicit sex...and all of the ensuing violent consequences in the kudzu-strangled, snake - rat- and armadillo-infested hole of the Devil's Punchbowl.
Keywords: Murder -- Fiction; Gambling and crime -- Fiction; Wilderness areas -- Mississippi -- Fiction; Mississippi -- Race relations -- Fiction; Natchez (Miss.) -- Fiction; Suspense fiction